Nursing education: creation of an academic league for urgent and emergency education (Research, Society and Development, 2020)
Academic leagues consist of extracurricular activities, centered on a specific theme, where the technical-scientific and humanistic training of members, the contribution to the care and promotion of health to the community, and the strengthening of students are developed actions. In this perspective, this study aimed to report the creation and implementation of an extension project entitled the Academic League of Trauma and Emergency, and its contributions to university education. This is an experience report on the implementation of the Academic League of Trauma and Emergency aimed at undergraduate Nursing students at a higher education institution in the interior of São Paulo. The activities include administrative meetings and educational activities, which include theoretical and practical training courses, aimed at league members or the community. For all academic league activities, members are encouraged and encouraged to participate actively, assuming a leadership, organization and execution role. The insertion of the Academic League of Trauma and Emergency in Nursing undergraduate courses proved to be an important technology for teaching contribution, in a way that enables the formation of critical, reflective and sensitized professionals with the theme.